Gogoli's Punishment as a Renewal of National Death Penalty Sanctions against Immigrants Committing Narcotics Criminal Acts in the Development of Criminal Law in Indonesia (Study Period of the Buton Sultanate) - Ali, La Ode Bunga; Mansyah, Muh Syutri (Law Research Review Quarterly, 2018)
At present, the Indonesian state is experiencing an unresolved narcotics problem. Various efforts to eradicate and prevent narcotics have been made, but they have not caused a deterrent effect in law enforcement. There are difficulties in eradicating at its roots, it is one of the obstacles experienced by our law enforcement officers, in this study using a normative juridical research method with a historical approach, a conceptual approach that has examined traditional criminal sanctions that were in force during the Buton Sultanate. and obstacles in the implementation of gogoli punishment. The results of this study indicate that the renewal of the national criminal law in relation to criminal sanctions can be sourced from customary law in effect in the Sultanate of Buton as intended is the gogoli punishment, while the concept of imposing a gogoli sentence is a rope wrapped around the body of the person sentenced and pulled in a way that the opposite direction until the endurance of his body lost or death, the sentence is included in the type of death sentence, this is relevant to immigrants who commit narcotics crime in Indonesia who have been sentenced several times to death sentence but apparently until now it still has no effect, the authors have the hope that the sentence can be applied nationally given the narcotics crime that occurred in almost all regions and will damage the morale of the nation's children today.